Modeling nitric oxide diffusion and plasticity modulation in cerebellar learning - Alessandra Maria Trapani; Carlo Andrea Sartori; Benedetta Gambosi; Alessandra Pedrocchi; Alberto Antonietti (APL Bioengineering)
Nitric oxide (NO) is a versatile signaling molecule with significant roles in various physiological processes, including synaptic plasticity and memory formation. In the cerebellum, NO is produced by neural NO synthase and diffuses to influence synaptic changes, particularly at parallel fiber-Purkinje cell synapses. This study aims to investigate NO's role in cerebellar learning mechanisms using a biologically realistic simulation-based approach. We developed the NO Diffusion Simulator (NODS), a Python module designed to model NO production and diffusion within a cerebellar spiking neural network framework. Our simulations focus on the eye-blink classical conditioning protocol to assess the impact of NO modulation on long-term potentiation and depression at parallel fiber-Purkinje cell synapses. The results demonstrate that NO diffusion significantly affects synaptic plasticity, dynamically adjusting learning rates based on synaptic activity patterns. This metaplasticity mechanism enhances the cerebellum's capacity to prioritize relevant inputs and mitigate learning interference, selectively modulating synaptic efficacy. Our findings align with theoretical models, suggesting that NO serves as a contextual indicator, optimizing learning rates for effective motor control and adaptation to new tasks. The NODS implementation provides an efficient tool for large-scale simulations, facilitating future studies on NO dynamics in various brain regions and neurovascular coupling scenarios. By bridging the gap between molecular processes and network-level learning, this work underscores the critical role of NO in cerebellar function and offers a robust framework for exploring NO-dependent plasticity in computational neuroscience.